Black and White Men and Women’s Relationships as seen through Soul On Ice by Leroy Eldridge Cleaver - KPOHOUE, FERDINAND (My University, 2017)
Leroy Eldridge Cleaver was born on August 1935 in Wabbaseka, Arkansas. Growing up, he witnessed his father beating his mother. As a teenager, Cleaver was charged with stealing a bicycle and sent to reform school. He would return for a second stay for selling marijuana. In 1954, he was sent to prison for possession of marijuana. During his incarceration, he began to develop his own political philosophy. After his release in 1957, he raped an unknown number of women, both black and white. He felt that his rapes of white women were "insurrectionary" rapes, justified by what African Americans had suffered under a system dominated by whites. In 1967, Cleaver joined the Black Panther Party as its minister of information. He became the voice of the activist group, coming up with attention-getting slogans and editing its newspaper. The next year, Soul on Ice, a collection of Cleaver's prison writings, was released and became a bestseller. This shows Cleaver’s ability to raise people’s awareness on some social events through literature. So in his literary works, he makes use of linguistic resources. Thus, under the banner of Pragmatics, this work analyzes the Speech Acts in twenty locutions randomly selected in the fourth chapter from page 155 to page 175. The description and interpretation of the linguistic resources seek to exude how the participants, state facts and express feelings and emotions. This study aims at exploring the speech acts involved in the speeches of characters in the novel “Soul On Ice” written by Eldridge Cleaver. The analysis has been done throughout Searle’s speech act framework.
Keywords: speech act; locutions; pragmatics; Blacks; Whites; men; women